Retrospective analysis of longitudinal melanonychia: A Chinese experience - Lyu, Anqi; Hou, Yinglong; Wang, Qiying (Frontiers in Pediatrics, 2023)
Objective: We aimed to analyze the clinical and histopathologic characteristics of LM, explore the differences between adults and children, and propose recommendations. Methods: Data on pigmentation, lentigo, subungual melanoma (SUM), and nail matrix nevus (NMN) were acquired for comparison. Results: Thumbs in children group were significantly lower (p = 0.006) than that of adults. Little fingers in children were more than adults, statistically significant (p = 0.025). The widths of adults were wider than children (p < 0.001), the duration and width were positively correlated (r = 0.474). There were more pigmentations in adults than children, the difference was statistically significant (p = 0.005). NMNs were reported in 56.1% of children and 34.3% of adults, the difference was statistically significant (p = 0.005). Adults had six SUMs, none in children, the difference was statistically significant (P = 0.006). The recurrence rate of adults was significantly higher than children (p = 0.019). Conclusion: The widths of bands increase with the course indicating that LM may be progressive. The four pathological types have different distributions with age, and each type requires different treatment. The lower recurrence rate in children suggests LM needs diagnosis and appropriate treatment as soon as possible.